Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1365-2796.2002.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking or nicotine replacement on cardiovascular risk factors and parameters of haemorheology

Abstract: Objectives. Cigarette smoking causes cardiovascular (CV) disease, but the relative roles of nicotine and other components of tobacco smoke remain unclear. We investigated the effect of stopping smoking, by using nicotine replacement therapy (NRT), on haemorheology parameters. Design. Open, parallel-group trial (intervention group and control smokers). Setting. Clinic within university department of pharmacology. Subjects. One hundred and ninety-seven males, aged 25-45 years, smoking >20 cigarettes per day. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 65 publications
(75 reference statements)
2
22
0
3
Order By: Relevance
“…The attenuation of IL-6 production by exogenous CO in vitro occurred even at very low concentrations of CO (50 ppm). For comparison, this concentration of CO is close to the levels that can routinely be measured in the exhaled breath of healthy individuals who smoke (30 ppm) (28).…”
Section: Discussionsupporting
confidence: 74%
“…The attenuation of IL-6 production by exogenous CO in vitro occurred even at very low concentrations of CO (50 ppm). For comparison, this concentration of CO is close to the levels that can routinely be measured in the exhaled breath of healthy individuals who smoke (30 ppm) (28).…”
Section: Discussionsupporting
confidence: 74%
“…87 Again haematocrit and white blood cell count decreased extensively in abstainers. 87 On a different account, Galea G et al observed highly significant differences in whole blood viscosity, plasma viscosity, plasma fibrinogen concentrations, packed cell volume and caboxyhaemoglobin concentrations between smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 95%
“…87 Again haematocrit and white blood cell count decreased extensively in abstainers. 87 On a different account, Galea G et al observed highly significant differences in whole blood viscosity, plasma viscosity, plasma fibrinogen concentrations, packed cell volume and caboxyhaemoglobin concentrations between smokers and non-smokers. 88 Smoking cessation leads quickly to improvement of clinical, functional and laboratory parameters such as reduced carboxyhaemoglobin, increased oxyhemoglobin and increased average expiratory flow between 25 -75% of vital capacity.…”
Section: Discussionmentioning
confidence: 95%
“…La position assise prolongée réalisant une compression veineuse poplitée et/ou fémorale, l'hémoconcen-tration liée à une mauvaise hydratation pendant le vol et une diminution de l'hygrométrie (> 20 %) sont autant de facteurs initiateurs d'une stase veineuse. En outre, le tabagisme (désor-mais interdit au cours du vol) accentue la viscosité sanguine et augmente le taux de fibrinogène circulant [13].…”
Section: Maladie Thromboembolique Du Voyageurunclassified